Throughput of cooperative HARQ protocols for underlay cognitive radio networks using adaptive and fixed transmit power. (14th October 2019) - Halima, Nadhir Ben; Boujemâa, Hatem
In this paper, we study theoretically and by simulations the throughput of cooperative hybrid automatic repeat request (HARQ) protocols for underlay cognitive radio networks (CRN). Both fixed and adaptive power transmission are studied. Different relay selection techniques with amplify and forward (AF) and decode and forward (DF) relaying are investigated. For fixed transmit power, some relays are not available due to interference constraints. The best relay is selected among the available ones. For adaptive transmit power, all relays adapt their power so that interference to primary receiver is always lower than a predefined threshold T . In this case, all relays will be available for retransmitting the secondary source packet. Both average interference power (AIP) and peak interference power constraints (PIP) are studied. We also analyse the effect of primary interference on secondary throughput.